Clinical Profile and Management of Uterovaginal Prolapse with Lower Urinary Tract Symptom (LUTS) - Begum, S; Sharmin, S; Sultana, P; Chowdhury, AN; Sultana, P; Nabi, S; Uddin, MN; Hasan, MM (Bangladesh Journal of Urology, 2012)
Genital prolapse affects the quality of life of many women during their pre-menopausal and post menopausal years. The aim of the study is to record the aetiological aspect, precipitating factors in the causation of genital prolapse. The objective is to evaluation of cases in terms of clinical profile, different modalities of treatment and the complication associated with prolapse. It is a prospective type of study was carried out in the Department of Obst. & Gynae in district hospital Comilla from January 2009 to December 2009. 72 cases of uterovaginal prolapse admitted in the study period were enrolled in this study. In this study most of the cases (36.11%) were in the age group between 51-60 yrs, having 5-9 children (54.16%) and early resumption of activity after delivery (52.77%), prolonged labour (22.22%) and chronic cough (27.77%) is the common cause. In this study maximum cases were poor (56.94%) and something coming down per-vagina (100%), urinary problem (72.22%) and backache (62.50%) is the main symptom. Most of the patient had 20 uterovaginal prolapse and vaginal hysterectomy with ant colporrhaphy with or without posterior colpoperiniorrhaphy is the main method of treatment. Bangladesh Journal of Urology, Vol. 14, No. 1, January 2011 p.26-30